2019
DOI: 10.30827/tsg-gsw.v9i17.8284
|View full text |Cite
|
Sign up to set email alerts
|

Prevalencia y factores de riesgo asociados al síndrome de burnout entre los profesionales del trabajo social en servicios sociales municipales en España

Abstract: La literatura científica internacional ha puesto de manifiesto una elevada prevalencia de burnout entre los profesionales del Trabajo Social. El objetivo de la presente investigación consiste en determinar la prevalencia de burnout, así como los factores demográficos asociados, entre los profesionales del Trabajo Social que desarrollan su actividad en el Sistema de Servicios Sociales. Se llevó a cabo un estudio de carácter transversal analítico sobre un total de 77 colegiados en los Colegios Profesionales de T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 34 publications
3
13
0
2
Order By: Relevance
“…In addition, the fact of having a stable partner has been statistically associated with higher levels of congruence in the reward area, which could lead to lower levels of burnout, according to previous research indicating a relationship between the lack of a partner and higher levels of burnout (Caravaca Sánchez et al, 2019).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In addition, the fact of having a stable partner has been statistically associated with higher levels of congruence in the reward area, which could lead to lower levels of burnout, according to previous research indicating a relationship between the lack of a partner and higher levels of burnout (Caravaca Sánchez et al, 2019).…”
Section: Discussionmentioning
confidence: 90%
“…The influence of sociodemographic factors on the emergence of burnout among social workers has also been analyzed, with divergent results. Some studies have found higher levels of emotional exhaustion among women (Caravaca Sánchez et al, 2019; Vilá Falgueras et al, 2015), and others among men (Domínguez Alonso et al, 2017). A similar situation occurs with marital status.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Romero-Martín et al (2020) also found that With regard to sex, many studies note that social work is a mostly female profession (Báñez, 2012), with women being found to display greater emotional exhaustion and depersonalization (Caravaca-Sánchez et al, 2019; Vilá et al, 2015) and to have a statistically more significant susceptibility to burnout (Caravaca-Sánchez et al, 2019; Gillespie, 2013; Kim et al, 2011) than their male coworkers.…”
Section: Introductionmentioning
confidence: 99%
“…Although the General Council of Social Work (2019) does not evaluate actual burnout using a specific, validated instrument, it does confirm that 39.9% of participants verbalize their symptoms of being stressed/overwhelmed and that one in three people (32.6%) exhibit job-related lack of motivation and exhaustion. Specific investigations on the burnout syndrome among social workers in Spain are scarce (Barría, 2003) although they arouse growing interest that has led to an increase in publications in recent years (Barrera et al, 2015;Caravaca-Sánchez et al, 2019;Caravaca-Sánchez et al, 2018;González-Rodríguez et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Specific investigations on the burnout syndrome among social workers in Spain are scarce (Barría, 2003) although they arouse growing interest that has led to an increase in publications in recent years (Barrera et al., 2015; Caravaca‐Sánchez et al, 2019; Caravaca‐Sánchez et al., 2018; González‐Rodríguez et al., 2020).…”
Section: Introductionmentioning
confidence: 99%